Application of frame for simultaneous lif and lii imaging in sooting flames using a single camera - Mishra, Yogeshwar Nath; Boggavarapu, Prasad; Chorey, Devashish; Zigan, Lars; Will, Stefan; Deshmukh, Devendra; Rayavarapu, Ravikrishna (Sensors, 2020)
In this article, the application of the FRAME (Frequency Recognition Algorithm for Multiple Exposures) technique is presented for multi‐species measurements in symmetric and asymmetric ethylene/air diffusion flames. Laminar Bunsen‐type and swirled diffusion flames are investigated to gain a better understanding of sooting combustion. For this purpose, simultaneous imaging is conducted in terms of Laser‐Induced Fluorescence (LIF) of Polycyclic Aromatic Hydrocarbons (PAH) and Laser‐Induced Incandescence (LII) of soot particles. Subsequently, the approach is utilized for simultaneous imaging of hydroxyl (OH)‐LIF and soot‐LII. Here, the modulated LIF‐ and LII‐signals are acquired together as a single sub‐image—with a single exposure utilizing the full sensor size of a single camera. By employing the frequency‐recognition algorithm on the single image, the LIF‐ and LII‐signals are spectrally isolated—generating two individual LIF-and LII‐images. The flame luminosity and out‐of‐focus light such as reflected surrounding laser light are detected as non‐modulated signals in the unprocessed image. These unwanted signals are suppressed using the image post‐processing, and, therefore, the image contrast of the two resulting images is improved. It is found that PAHs mainly exist in the inner region near the burner and are surrounded by soot. The majority of the OH is distributed on the outer edges of the flame— representing the reaction zone and soot‐oxidation region of the flame.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Combustion; Flame species; Laser‐Induced fluorescence; Laser‐induced incandescence; Multispectral imaging; Soot; Structured illumination